2000
DOI: 10.1111/1467-9817.00115
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reading speed and reading patterns on the understanding of text read from screen

Abstract: With increasing use of the World Wide Web, rapid scanning or skimming of material on screen has become a frequent activity. However, the outcome of this method of reading has not been thoroughly investigated. Using a range of question types, comprehension was measured after reading from screen at both a normal and fast reading speed. In addition, by automatically recording how readers scrolled through each document, reading patterns were explored. A speed-accuracy trade-off was found and, in general, the recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 3 publications
5
46
1
2
Order By: Relevance
“…Speci"cally in relation to scrolling, distraction may be caused by the mechanics of the movements (Hansen & Haas, 1988;O'Hara & Sellen, 1997). This proposal is consistent with Dyson and Haselgrove (2000) who found that the overall time spent pausing between scrolling was the best predictor of comprehension. When reading at normal speed, the readers with higher comprehension scores were those who spent more time pausing between scrolling and made fast and frequent scrolling movements.…”
Section: Scrolling Patternssupporting
confidence: 72%
See 2 more Smart Citations
“…Speci"cally in relation to scrolling, distraction may be caused by the mechanics of the movements (Hansen & Haas, 1988;O'Hara & Sellen, 1997). This proposal is consistent with Dyson and Haselgrove (2000) who found that the overall time spent pausing between scrolling was the best predictor of comprehension. When reading at normal speed, the readers with higher comprehension scores were those who spent more time pausing between scrolling and made fast and frequent scrolling movements.…”
Section: Scrolling Patternssupporting
confidence: 72%
“…However, this result could be accounted for by a speed-accuracy trade-o!, as the rate of reading print was signi"cantly faster than reading from screen. Dyson and Haselgrove (2000) also found a trade-o! between reading rate and comprehension when readers were trained to read from screen at a faster speed.…”
Section: Reading Speed Reading Rate and Comprehensionmentioning
confidence: 88%
See 1 more Smart Citation
“…A more elaborate test of comprehension was used in this study. A set of multiple choice questions requiring recall of different types of material was developed by Dyson and Haselgrove (2000) and used in the 2001 study to compare line lengths. Differences in comprehension were not cancelled out by differences in reading rate as there was no speed-accuracy trade-off.…”
Section: Comprehension Of Characters Per Linementioning
confidence: 99%
“…A wealth of research evidence exists to suggest that spatial encoding takes place during the reading process, and that this is an integral function when individuals build a mental representation of the location of textual information whilst reading (Kennedy, 1992;Piolat et al, 1997;Fischer, 1999). A number of studies support the notion that the assignation of geographical locators during reading is easier when reading on paper compared with the computer (Wright & Lickorish, 1984;Dyson & Haselgrove, 2000;Pommerich, 2004). O'Malley & Stanton (2004) suggest that physical activity helps to build representational mappings.…”
Section: Sense Of Textmentioning
confidence: 99%